2020
DOI: 10.3847/1538-4357/ab6131
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-energy Cosmic-Ray Interactions as the Origin of Very High-energy γ-Rays from BL Lacertae Objects

Abstract: We explain the observed multiwavelength photon spectrum of a number of BL Lac objects detected at very high energy (VHE, E 30 GeV), using a lepto-hadronic emission model. The one-zone leptonic emission is employed to fit the synchrotron peak. Subsequently, the SSC spectrum is calculated, such that it extends up to the highest energy possible for the jet parameters considered. The data points beyond this energy, and also in the entire VHE range are well explained using a hadronic emission model. The ultrahigh-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 112 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…Thus, there exists a degeneracy in explaining the blazar SED, which can be lifted by future multimessenger observations. Ultra-high-energy (UHE) protons, if accelerated, can escape the jet when the escape timescale is shorter than the acceleration time (see, e.g., Das et al 2020). These UHECRs can interact with photons from the cosmic microwave background (CMB) and extragalactic background light (EBL) to produce secondary neutrinos and γ rays with a hard spectrum along the line-of-sight Kalashev et al 2013;Das et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there exists a degeneracy in explaining the blazar SED, which can be lifted by future multimessenger observations. Ultra-high-energy (UHE) protons, if accelerated, can escape the jet when the escape timescale is shorter than the acceleration time (see, e.g., Das et al 2020). These UHECRs can interact with photons from the cosmic microwave background (CMB) and extragalactic background light (EBL) to produce secondary neutrinos and γ rays with a hard spectrum along the line-of-sight Kalashev et al 2013;Das et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…• The contribution of Das [51] showed that in principle extreme BL Lac objects (those with energy peaks at very high energies with respect to the rest of the BL Lac population) can be sources of UHECRs and that the UHECR contribution can help fit the source spectra nicely. But in general one does not expect neutrinos from these sources (there are too few).…”
Section: Pos(icrc2021)043mentioning
confidence: 99%
“…For detailed paramter values of all the sources considered in the study, please see Ref. [8]. interactions with synchrotron and IC photons inside the jet are compared with the escape timescale esc and the acceleration timescale acc (cf.…”
Section: Pos(icrc2021)1002mentioning
confidence: 99%
“…Here we present the results for only 1ES 0229+200. Please refer to [8] for a detailed and fuller analysis.…”
Section: Pos(icrc2021)1002mentioning
confidence: 99%
See 1 more Smart Citation